Teachers’ Perspectives on the Integration of Culture and EFL - Triyanti Abdulrahman; Novi Rusnarty Usu; Zulkifli Tanipu (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2016)
This study is aimed to investigate teachers’ opinion and their attitudes toward the integration of culture and English language education. More specifically, this study explores how and to what extent these opinions and attitudes are reflected in their classroom applications. Data were collected from 31 teachers of English Department at one of universities in Indonesia using questionnaire, interview, and observation. Findings revealed that teachers were willing to support the language and cultural objectives, but they had conflicts when having to prioritize language teaching or cultural teaching. Teachers informed that limited class time, curriculum requirements, lack of cultural issues in the textbooks, and their lack of cultural knowledge were the main constraints for the integration of cultural teaching into EFL. This study shows the importance of integrating culture & intercultural dimension into EFL instruction in order to help facilitate both language learning and effective communication.